Review: From multi-scale conceptualization to a classification system for inland groundwater-dependent ecosystems - Bertrand, G; Goldscheider, Nico; Gobat, Jean-Michel; Hunkeler, Daniel (My University, 2012)
Aquifers provide water, nutrients and energy with various patterns for many aquatic and terrestrial ecosystems. Groundwater-dependent ecosystems (GDEs) are increasingly recognized for their ecological and socio-economic values. The current knowledge of the processes governing the ecohydrological functioning of inland GDEs is reviewed, in order to assess the key drivers constraining their viability. These processes occur both at the watershed and emergence scale. Recharge patterns, geomorphology, internal geometry and geochemistry of aquifers control water availability and nutritive status of groundwater. The interface structure between the groundwater system and the biocenoses may modify the groundwater features by physicochemical or biological processes, for which biocenoses need to adapt. Four major types of aquifer-GDE interface have been described: springs, surface waters, peatlands and terrestrial ecosystems. The ecological roles of groundwater are conditioned by morphological characteristics for spring GDEs, by the hyporheic zone structure for surface waters, by the organic soil structure and volume for peatland GDEs, and by water-table fluctuation and surface floods in terrestrial GDEs. Based on these considerations, an ecohydrological classification system for GDEs is proposed and applied to Central andWestern-Central Europe, as a basis for modeling approaches for GDEs and as a tool for groundwater and landscape management.
Keywords: Groundwater-dependent ecosystem; Ecology; Western-Central Europe; Conceptual models; Aquifer-biocenosis interface